Assume that the number is n.
sum of twice the number and 15 means that you will first multiply the number by 2 then add 15.
the equation us:
2n + 15 = -42
2n = -42-15
2n = -57
n = -28.5
Answer:
(-2,1)
Step-by-step explanation:
solution:
We are going to use this property: P(A U B) = P(A) + P(B) – P(AB)
First we treat (A U B) as one event as follows:
P( (A U B) U C) = P( A U B ) + P(C) – P((A U B)C)
= P( A U B ) + P(C) – P(AC U BC)
= P(A) + P(B) – P(AB) + P(C) – P(C) – P(AC U BC )
=P(A) + P(B) – P(AB) + P(C) –P(AC) – P(BC) + P(ABC)
= P(A) + P(B) + P(C) – P(AB) – P(AC) – (BC) + P(ABC)